Frequency dependence of dynamic compliance in patients with rheumatoid arthritis. Issue 6 (December 1979) - Hills, E A; Davies, S; Geary, M
Abstract : An investigation of lung function was carried out in 99 randomly selected patients with calssic or definite rheumatoid arthritis and in 60 control subjects matched for age, sex, and smoking habits. Mean FEV1 and mean VC were both significantly lower in the rheumatoid patients due to significant differences for women but mean FEV/VC ratio was 73.0% in the rheumatoid group and 72.1% in the control. Steady-state transfer factor was significantly greater in the normal men than in the comparable rheumatoid group, but there was no difference for women. After excluding patients with FEV1 less than 80% predicted normal and patients with low compliance, 72 rheumatoid patients and 45 controls provided series of tracings that could be assessed for a fall in Cdyn of 20% between 20 cycles and 60 cycles a minute. Dynamic compliance was not significantly different in any group at any rate of respiration. Fourteen of 72 rheumatoid patients and three of 45 controls showed frequency dependence (FDC). After the age of 50 the prevalence in the rheumatoid groupwas 11/38 and in the control group 2/27. This difference was significant (P less than 0.05). FDC was not consistently related to other abnormalities of lung function or to the duration, severity, or treatment of the rheumatoid arthritis. In various categories of smoking habits, dust exposure, or allergic tendency, the prevalence was always greater in the rheumatoid group. This provides evidence of patchy involvement of small airways, or alveoli and connective tissue, by the rheumatoid process.